2011
DOI: 10.3109/10903127.2011.569849
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mortality in Injured Adults Transported by Helicopter Emergency Medical Services

Abstract: Background. Some studies have shown improved outcomes with helicopter emergency medical services (HEMS) transport, while others have not. Safety concerns and cost have prompted reevaluation of the widespread use of HEMS. Objective. To determine whether the mode of transport of trauma patients affects mortality. Methods. Data for 56,744 injured adults aged ≥18 years transported to 62 U.S. trauma centers by helicopter or ground ambulance were obtained from the National Sample Program of the 2007 National Trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 41 publications
2
55
0
1
Order By: Relevance
“…In another study using the 2007 NTDB data, Sullivent et al 10 reported a lower odds of death for patients 18 to 54 years old transported by helicopter (OR, 0.51; 95% CI, 0.44-0.60; P < . 001).…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study using the 2007 NTDB data, Sullivent et al 10 reported a lower odds of death for patients 18 to 54 years old transported by helicopter (OR, 0.51; 95% CI, 0.44-0.60; P < . 001).…”
Section: Commentmentioning
confidence: 98%
“…[9][10][11] Although each of these studies concluded that helicopter transport was associated with improved odds of survival, they also reported limitations to their conclusions because of the lack of testing for the assumptions of a regression model, and none was able to account for the differences in how patients were assigned treatments (helicopter or ground transport). Additionally, the high proportion of missing data in the NTDB may have introduced bias.…”
mentioning
confidence: 99%
“…We have found quite some literature that shows helicopter transport to reduce mortality in trauma patients [7][8][9][10], and although this was not within the scope of this study, we believe that our results combined with this literature justify a recommendation to use transport by the HEMS helicopter more often in the Netherlands rural setting.…”
Section: Resultsmentioning
confidence: 58%
“…A study conducted in the USA, whose objective was to determine whether the mode of transport of adult trauma patients affected patient mortality, showed that the chances of death were 39% lower when transport occurred made by air service as compared to those transported by land (21) .…”
Section: Discussionmentioning
confidence: 99%